A study of treatment modalities in breast cancer patients with help of triple marker test - Kelkar, Nilay M.; Ghuge, Anita (International Journal of Research in Medical Sciences, 2025)
Background: Breast cancer is a leading cause of cancer-related morbidity and mortality worldwide. Advances in early diagnosis and molecular profiling have significantly improved treatment outcomes. The triple marker test, which assesses estrogen receptor (ER), progesterone receptor (PR), and human epidermal growth factor receptor 2 (HER2) status, plays a crucial role in classifying breast cancer subtypes and guiding treatment decisions. Personalized treatment approaches based on molecular characteristics enhance the effectiveness of hormone therapy, targeted therapy, and chemotherapy. Methods: This prospective study evaluates the impact of the triple marker test in determining breast cancer treatment modalities. Patients were classified based on their ER, PR, and HER2 status to assess their response to various therapeutic interventions. Data collection included clinical examinations, histopathological analysis, and treatment outcomes following neoadjuvant therapy, surgery, and adjuvant therapies. Results: Findings indicate that ER/PR-positive patients benefit significantly from hormone therapy, while HER2-positive cases show improved outcomes with targeted agents like trastuzumab. Triple-negative breast cancer (TNBC) remains a therapeutic challenge, often requiring aggressive chemotherapy. The study also highlights the role of neoadjuvant therapy in reducing tumor size, facilitating breast-conserving surgery (BCS), and improving overall prognosis. Conclusions: Molecular profiling using the triple marker test is instrumental in optimizing breast cancer treatment strategies. Personalized treatment plans based on receptor status enhance survival rates and quality of life (QoL). Integrating biomarker-driven approaches into clinical practice ensures more precise and effective breast cancer management.